1991
DOI: 10.1080/00029157.1991.10402967
|View full text |Cite
|
Sign up to set email alerts
|

Hypnosis and the Treatment of Huntington's Disease

Abstract: Huntington's Disease is an inherited fatal disorder of the central nervous system. Literature on the hypnotic treatment of this disease is extremely sparse. We treated two patients with Huntington's Disease using a wide variety of hypnotic interventions. One patient was treated for a number of years and the other for 10 consecutive sessions. We discuss the continuously interacting cycle between the primary physical symptoms caused by the disease and the secondary psychological symptoms. Hypnotic techniques and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Witz et al [41] used various hypnotic interventions to treat two patients with Huntington's disease, a disorder of the central nervous system. It was found that hypnosis enhanced self-monitoring skills which were lost.…”
Section: The Role Of Clinical Hypnosis In Self-observationmentioning
confidence: 99%
“…Witz et al [41] used various hypnotic interventions to treat two patients with Huntington's disease, a disorder of the central nervous system. It was found that hypnosis enhanced self-monitoring skills which were lost.…”
Section: The Role Of Clinical Hypnosis In Self-observationmentioning
confidence: 99%
“…Couple-based interventions seem more beneficial than individual approaches to manage relational difficulties, although they can be complemented by individual-based interventions. [86], Moldawsky [87], Witz & Kahn [88] and Gravitz [89] underlined that motivation, trust, positive expectations and attitude towards hypnosis (vs. reluctancy, skepticism, anxiety, fear of losing control) are crucial factors for evaluating the level of hypnotizability of individuals and enabling them to truly benefit from it. For future research, it is essential for professionals to be better trained at talking about and explaining what hypnosis is, to take more time to work on the representations of couples by providing all the elements of understanding and reassurance to help couples experience it with more confidence, calm and efficiency [86,90].…”
Section: Acceptability Of Interventionmentioning
confidence: 99%
“…In this study, half of the couples had a previous experience of hypnosis or equivalent, which may influence acceptability and hypnotizability and how they benefit from it thanks to a more confident and positive attitude towards hypnosis, more positive motivation and expectations and less apprehension [86][87][88][89]. In a larger sample, it might be interesting to compare the influence of previous practice on the outcomes with the absence thereof.…”
Section: Limitationsmentioning
confidence: 99%